Analisis Potensi Bahaya (Unsafe Action & Unsafe Condition)Dan Pengendalian Risiko Di Proyek Konstruksi Manggarai “Main Line 1” Phase II Nindya Citra Kharisma KSO Jakarta Selatan - Siska Melati; Herlina Herlina (Jurnal Persada Husada Indonesia, 2021)
The development of the construction service industry has progressed, there are many hazards that workers can encounter in the workplace.The existence of this hazard can lead to accidents, so the implementation of the K3 program is a must for companies, especially Nindya Citra Kharisma KSO.This study aims to determine the analysis of potential hazards (unsafe action & unsafe condition) and risk control in the Manggarai "Main Line 1" Phase II construction project Nindya Citra Kharisma KSO.This study uses a qualitative design and is more based on phenomenological characteristics that prioritize appreciation (verstehen).Data were obtained by conducting interviews, direct observation and document review.The focus of the research is the potential hazards of unsafe action (human factors) including the causes of fatigue and behavior, the potential hazards of unsafe conditions (environmental factors) including the workplace and equipment, and risk control, namely administrative and personal protective equipment.The results showed that the potential danger of unsafe action, the cause of fatigue; there is no vacation, the demands of work tasks can reduce work motivation, noise reaches 86.6 dAB > NAV, work with repetitive movements and the use of large muscles can cause boredom and fatigue.Behavior; Workers do not attach the hook body harness to the lifeline, most of the workers are active smokers, there is no smoking area and there are still workers who smoke while working.Potential hazards in unsafe conditions, workplace; work at the height of the strill structure as high risk with the potential danger of falling and being crushed.Lifeline installation has not been carried out optimally.Equipment; equipment operator must be certified.Risk control, administrative; work shift arrangements are not enforced in the company.PPE; The company does not provide ear protection (ear muff & ear plug).Suggestions: provide a smoking area, provide ear protection equipment, impose sanctions on workers who take unsafe action.